HOMOCYSTEINЕ AFTER LIVER TRANSPLANTATION IN CHILDREN - O. P. Shevchenko; V. V. Dolgov; O. E. Gichkun; N. V. Kuncevich; O. M Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2012)
The research plasma levels of homocysteine (Hcy) in 99 children with congenital and hereditary diseases of hepatobiliary system was performed before liver transplantation. 27% of patients had hyperhomocysteinemia. There was correlation between Hcy levels and sCD40L. High (≥5.1 μmol/L) pretransplant concentration of Hcy is one of the negative factors that affect function of the liver graft in the early post-transplant period.